Additive manufacturing 3D printing for prototyping and manufacturing - Gebhardt, Andreas 1953-; Hötter, Jan-Steffen 1987- (Hanser, 2016)
The use of additive manufacturing for the direct production of finished products is becoming increasingly important. The method not only reduces the demands on industrial infrastructure, but also opens up new perspectives in terms of decentralized production and customer inclusive individualized production (customization, cyberproduction). Oriented towards the practitioner, in this book the basics of additive manufacturing are presented and the properties and special aspects of industrially available machines are discussed. From the generation of data to the forming method, the complete process chain is shown in a practical light. In particular, the following additive manufacturing technologies are discussed: - Polymerization (e.g., stereolithography) - Sintering and melting (e.g., laser sintering) - Layer laminate method (e.g., laminated object manufacturing, LOM) - Extrusion (e.g., fused deposition modeling, FDM) - 3D printing Applications for the production of models and prototypes (rapid prototyping), tools, tool inserts, and forms (rapid tooling) as well as end products (rapid manufacturing) are covered in detailed chapters with examples. Questions of efficiency are discussed from a strategic point of view, and also from an operational perspective.